Análise comparativa da eficiência de filtros lentos com meios filtrantes convencional e não convencionais - Lima, Anderson de Jesus (2020)
Slow filtration is one of the most indicated water treatment technologies to serve rural/isolated communities, given their simplicity of construction, maintenance, operation and efficiency, especially in the removal of pathogens. To work around the raw water quality requirements that these systems require, you can change the filter medium settings, and thus achieve superior performance. In this sense, several studies indicate the benefits of applying intermediate layers of materials other than sand in the filter environment, especially some types of residues, whose surface area, porosity and adsorption can contribute to the removal of contaminants during filtration. In addition, the application of waste as alternative filter media has an environmental and economic appeal, since it adds value to what was previously discarded and characterized as environmentally sustainable destination. Thus, considering the gains obtained by applying materials other than sand as a filter medium, this work aims to compare the slow filter efficiency consisting of conventional filter medium with slow filters with filter media not modified with easily accessible waste. To this end, a pilot system with six filter was developed: a conventional sand filter (FLC), with coconut fiber filter medium (FLFC), sand with intermediate layer of coconut fibers (FLSFC), sand with intermediate layer of wood residue sawdust (FLSM), sand with intermediate layer of homemade charcoal cork stoppers (FLSCV), and sand with intermediate layer of ceramic residue (FLSRC), all with support layer of graduated crushes. The filters operated with descending flow, with a rate of 3.0 m³/m².day ±10% continuously and were fed groundwater with the addition of 1.2% sewage. The sand and gravel sums used were characterized by granulometric analysis and dimensional analysis, respectively, while unconventional materials were characterized based on the determination of apparent density, apparent porosity and water absorption capacity. Additionally, the main microorganisms present in the biological layer were identified. With the exception of charcoal that presented low apparent porosity, all materials used presented high water absorption capacity and porosity, especially coconut fibers that presented higher value for these two parameters. Regarding the efficiency of the systems, the results indicate that there are no statistically significant differences between conventional filter and filters with residues. However, filters with granular materials, FLSCV and FLSRC showed greater apparent color removal and turbidity among all filters, including the control filter. While filters with filter layers of organic natural waste were more effective in removing total coliforms and thermotolerant. Moreover, the individuals found in the biological layer of the filters did not differ from those reported in the literature. Thus, filters modified with residues demonstrated performance comparable to conventional slow filter, which justifies their use as a filter medium in regions with high production of these residues and/or with little availability of sand.